Macrocycle-Based Hydroxamate Ligands for Complexation and Immunoconjugation of (89)Zirconium for Positron Emission Tomography (PET) Imaging - Boros, Eszter (Chempluschem, 2016)
Four novel chelators (L1–L4) and their (89)zirconium complexes were prepared and compared with the (89)zirconium desferrioxamine B (DFO) complex. The new chelates are based on 1,4,7,10-tetraazacyclododecane (cyclen) and 1,4,8,11-tetraazacyclotetradecane (cyclam) scaffolds and present either three or four hydroxamate arms for coordination with Zr(4+) ions with coordination numbers between six and eight. The 89Zr–L4 complex showed similar stability to that of (89)Zr–DFO when incubated in either rat blood plasma or ethylenediaminetetraacetic acid challenge experiments. Positron imaging and biodistribution studies in mice showed that (89)Zr–L4 had similar pharmacokinetic behavior to that of (89)Zr–DFO, with rapid renal elimination and low residual activity in background tissues. A bifunctional version of L4 (L5) was synthesized and conjugated to trastuzumab; an anti-HER2/neu antibody. Immunopositron emission tomography imaging and biodistribution with (89)Zr–L5–trastuzumab revealed high tumor to background ratios (tumor/blood ratio: 14.2 ± 2.25) and a high tumor specificity that was comparable to the performance of (89)Zr–DFO–trastuzumab.